THE EFFECT OF LEG MUSCLE STRENGTH TRAINING ON SQUATTING LONG JUMP ABILITY IN STUDENTS OF SENIOR HIGH SCHOOL 1 KUTACANE CLASS XI SCHOOL YEAR 2024/2025 - Zaini Hasan (CV Naskah Aceh, 2024)
The research entitled “The effect of training ”Limb Muscle Strength on the ability of long jump squatting style in SMA Negeri 1 Kutacane Class XI Students of the 2024/2025 Academic Year